STRENGTHENING THE MANAGEMENT OF SECONDARY DATA-BASED ISLAMIC EDUCATION IN JEPARA - Ahmad Sufyan; Sukarman Sukarman; Muhammad Sofyan Atsauri; Muhammad Aris Kurniawan (Universitas Islam Negeri (UIN) Sumatera Utara, 2026)
This research aims to analyze and formulate a conceptual model of Islamic Education Management based on secondary data in Jepara Regency by integrating three main issues, namely mapping Madrasah Diniyah, access to educational assistance through the Smart Indonesia Program, and empowering religious teachers through MANDIRI MADINQu. The research uses a descriptive qualitative approach with a document study design. Data was collected from the statistics table of the Central Statistics Agency of Jepara Regency, official publications of the Ministry of Religion, government regulations, credible news, and relevant academic literature. Data analysis is carried out through document content analysis, descriptive analysis, source criticism, and source triangulation. The results of the study show that Jepara has a wide network of Madrasah Diniyah, but the distribution is not evenly distributed. By 2025, there will be 684 Madrasah Diniyah in 16 sub-districts, with the highest concentration in Batealit, Mayong, Tahunan, Kedung, and Bangsri, while Karimunjawa has the smallest number. The Indonesia Pintar program reaches 17,799 madrasah students and strengthens the dimension of access to education. MANDIRI MADINQu shows a model of teacher empowerment through economic support, mentoring, technical guidance, and institutional partnerships. The resulting conceptual model relates data inventory, institutional mapping, access diagnosis, teacher empowerment, coordination, and document-based evaluation.